Final report of the CCQM-K145: toxic and essential elements in bovine liver - Wang, Jun; Chao, Jingbo; Wei, Chao; Li, Haifeng; Wang, Qian; Song, Panshu; Lu, Hai; Zhou, Yuanjing; Tang, Yichuan; Wang, Song; Yang, Lu; Nadeau, Kenny; et al. (IOP Publishing, 2020)
Liver plays a major role in metabolism and acts as a source of energy for the body by storing glycogen. With the growing interest and investigation in the biological effects in recent years, it is important and necessary to develop accurate and comparable analytical methods for elements in bio-samples. It has, however, been 10 years since the tissue sample (bovine liver) of CCQM-K49 key comparison. The purpose of CCQM-K145 is to ensure the comparable and traceable measurement results for essential and toxic elements such as P, S, Zn, Mn, Ni, Mo, Sr, Cr, Co, Pb, As and Hg in bovine liver among NMIs and other designated measurement bodies worldwide. The comparison was agreed by IAWG as 6th IAWG Benchmarking Exercise with Zn and Ni as exemplary elements at the meeting in Korea in the early October 2016. The results of CCQM-K145 are expected to cover the measurement capability and support CMCs claiming for inorganic elements in the similar biological tissue materials and food samples. 30 NMIs and DIs registered in CCQM-K145. With respect to the methodology, a variety of techniques such as IDMS, ICP-OES, ICP-MS(non-ID), AAS and NAA were adopted by the participants. For Zn, Ni, Sr, Pb and Hg measurements, most participants chose ID-ICP-MS method, which showed the better performance in terms of consistency and reliability of the measurement results. In aspect of the traceability for the measurement results in CCQM-K145, most participants used their own (in house) CRMs or other NMI's CRMs to guarantee trace to SI unit. Most participants used similar matrix CRMs for quality control or method validation. Base on different statistic way to calculate the reference mass fraction values and associated uncertainties for each measurand, removal of the suspected extreme values, and discussion at the IAWG meetings, the median values are proposed as the KCRV for Zn, Ni, Mn, Mo, Cr, Pb and Hg; the arithmetic mean values are proposed as the KCRV for P, S, Sr, Co and As. In general, the performances of the majority of CCQM-K145 participants are very good, illustrating their measurement capabilities for Zn, Ni, P, S, Mn, Mo, Sr, Cr, As, Co, Pb and Hg in a complex biological tissue matrix. Bovine liver contains many kinds of nutrients and microelements, it can be regarded as a typical representative material of biological tissue and food. In CCQM-K145, the analytes involved alkali metals and transition elements, metalloids / semi-metals and non metals with a range of mass fraction from mg/g to μg/kg. CCQM-K145 also tested the ability of NMIs/DIs to determine elements that were easy to be lost and polluted, and interfered significantly. The chemical pretreatment methods of samples used in the comparison is suitable for general food and biological matrix samples. A variety of measurement methods used in the comparison represent the main instrumental technology for elemental analysis. Therefore, for supporting CMC claim, CCQM-K145 is readily applicable to measurement of more elements in a wide range of biological materials (including liquids and solids) and meat products. Main text To reach the main text of this paper, click on Final Report . Note that this text is that which appears in Appendix B of the BIPM key comparison database kcdb.bipm.org/ . The final report has been peer-reviewed and approved for publication by the CCQM, according to the provisions of the CIPM Mutual Recognition Arrangement (CIPM MRA).